Produção, crescimento e absorção de nutrientes pela melancia submetida a diferentes salinidades da água de irrigação e doses de nitrogênio - Costa, Andréa Raquel Fernandes Carlos da (Universidade Federal Rural do Semi-Árido, 2011)
The use of saline water in agriculture has increased in the Northeast due to low availability of good quality water for irrigated agriculture, being the selection of tolerant hybrids to salinity and the use of fertilization nitrogen, an alternative to avoid losses of income and reduce the effect of salinity on nutritional status of plants. So, the objective this work was evaluate the production, the grow and the absorption of cultivars of watermelon under different salinities of irrigation water and doses of nitrogen applied by fertigation in the region of Mossoró in the State of Rio Grande do Norte. The treatments studied consisted of applying irrigation water with five electrical conductivities (CE1 = 0,57, CE2 = 1,36, CE3 = 2,77, CE4 = 3,86 and CE5 = 4.91 dS m-1) and three doses of N (48, 96 and 144 kg ha-1), arranged in factorial scheme 5x3 and randomized in blocks design with four replications. It was evaluated the growth and the accumulated nutrient contents in plants of two cultivars of watermelon and the productivity and its components and the fruit quality of three cultivars of watermelon. Data were subjected to regression analysis to the salinity factor and for the factor nitrogen the averages were compared by Tukey test at 5% probability. The accumulation of nutrients studied in watermelon plants irrigated with water of lower electrical conductivity occurred in the following order: K>N>P. The nutrients were affected by CEa there is a loss for higher CEa of 35,8% and 29,1 % in the absorption of P and K respectively and of 94,5% in the absorption of N to Shadow and Quetzali cultivars. The highest values of productivity and its components were obtained with water of lower electrical conductivity. There wasn´t significant effect of nitrogen doses in the productivity of Shadow and Quetzali cultivars, while the Leopard cultivar presented commercial and total productivity and number of commercial fruits larger for the dose of nitrogen N2. The average mass of fruits e the number of fruits influenced the loss of income of production of watermelon cultivars studied. The nitrogen doses didn´t influence the soluble solids content in the watermelon cultivars studied. Only the Shadow cultivar responded to the effect of electrical conductivity of irrigation water on the soluble solids of the fruits.
Production, growth and absorption of nutrients by watermelon under different salinities of irrigation water and doses of nitrogen
Keywords: Citrullus lanatus; march of absorption; fertigation; Citrullus lanatus; marcha de absorção; fertirrigação; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE SOLO E AGUA::IRRIGACAO E DRENAGEM